Collaboration between Company and Local Institutions in Implementing the CSR Home Renovation Program (A Case Study of PT Semen Padang in Limau Manis Selatan Urban Village) - Azzahra, Maesy Hasni; Wialdi, Putri Febri (The Future of Education Journal, 2025)
This research focuses on examining how PT Semen Padang cooperates with local institutions to carry out its Corporate Social Responsibility (CSR) initiative for home renovation in Limau Manis Selatan, Pauh District, Padang City. The program represents the company’s social commitment to improving community welfare by providing decent housing for low-income families. This research employs a qualitative descriptive approach. Data were collected through interviews, observation, and documentation involving key informants from PT Semen Padang’s CSR division, the Forum Nagari, the Department of Housing and Settlement, and program beneficiaries. The results show that the collaboration between PT Semen Padang and the Forum Nagari was relatively effective in supporting the implementation of the CSR program. The program has had a positive impact on improving housing quality and community welfare. However, several challenges remain, such as limited funding, restricted beneficiary coverage, and a lack of transparency in the verification process. Enhanced coordination, transparency, and community participation are needed to ensure the sustainability and accuracy of the CSR program implementation.